Brazilian Portuguese lá in the CP-domain: a Cartographic analysis - PEREIRA, Bruna Karla; RAMOS, Jânia Martins (Revista da ABRALIN, 2013)
This paper aims at investigating Brazilian Portuguese ‘lá’ (‘there’) in structures with rhetorical question, imperative, directive, emphatic assertion, and predicative. We argue that, in these constructions, ‘lá’ is merged in the specifier of FocusP and ForceP in the CP- cartography. This proposal is based both in the F-Spec Theory (CINQUE, 1999) and in the cartographic project (RIZZI, 1997; CINQUE & RIZZI, 2008). The former claims that AdvPs are merged in the specifier of functional categories. The latter identifies a domain to the left of the IP which is made up by a range of functional categories facing both discourse and syntax.